THE ISLAMIZATION OF KNOWLEDGE IN ENGLISH LANGUAGE TEACHING - Djamdjuri, Dewi Suriyani; Redjeki, Indah Sri (ENGLISH JOURNAL, 2017)
The revolution of science starts with the revelation of Qur?an. Qur?an states about the relationship between God and the world of nature, so do the world of nature and the offspring of Prophet Adam. In the Qur?an, it is stated about Divine Name Ar-Rahman, the Most Merciful, which is viewed, has close relationship with nature. The encouragement in Qur?an will build some positive behaviors of human. Any information from Qur?an becomes precious materials to study, seek and think deeply. It is all about the evidence from the Qur?an. There are so many samples from the verses of the Qur?an that talk about science and knowledge. The aim of this article is to convey some messages from the Qur?an and from some of Islamic scholars. Various studies have been accomplished. Islamization of knowledge in all fields has close relationship with one?s understanding towards the Islamic belief, as Islam is a religion signifies on right-thinking, right-speaking, and right-doing. So the Islamization of knowledge means to protect Muslims from the knowledge that is contaminated, misleading and causes errors. It will lead to safety, kindness, justice, and the power of faith.